The globalization of human rights - Coicaud, Jean-Marc; Doyle, Michael, 1948-; Gardner, Anne-Marie (United Nations University Press, 2003)
This work focuses on the imperatives of justice at the national, regional, and international levels through an analysis of civil, political, economic, and social rights.
"The product of a research project conducted under the auspices of the Peace and Governance Programme of the United Nations University"--Page vii
Keywords: Human rights.; Civil rights.; Political rights.; Globalization.; Human Rights; Droits de l'homme (Droit international); Droits politiques.; Mondialisation.; globalism.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; Droits civils.; Droits de l'homme.; Civil rights; Globalization; Human rights; Political rights; Menschenrecht; Mensenrechten.; Internationalisatie.; princeton <NJ, 1999>